Cold-adapted protease enables quantitation of surface proteins in the absence of membrane trafficking. (January 2017) - Ahmad, Faraz; Coleman, Sarah Kate; Kaila, Kai; Blaesse, Peter
Protocol Summary: We report here an improved method for analyzing protein surface expression utilizing a cold-adapted trypsin. Preservation of activity of the enzyme at 0–4°C permits modification of the protease method of surface analysis to temperatures at which trafficking of mammalian plasmalemmal proteins is blocked. This is an important advantage over established trypsin-cleavage protocols. Moreover, the method is less time-consuming than surface biotinylation.